2017
DOI: 10.1109/tns.2017.2754948
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Damage in Silicon Photonic Mach–Zehnder Modulators and Photodiodes

Abstract: Radiation-hard optical links are the backbone of read-out systems in high-energy physics (HEP) experiments at CERN. The optical components must withstand large doses of radiation and strong magnetic fields and provide high data rates. Radiation hardness is one of the requirements that become more demanding with every new generation of HEP experiment. Previous studies have shown that vertical cavity surface emitting lasers, on which the current optical links are based, will not be able to withstand the expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…The slab thickness of these standard modulators is 120 nm, providing a good confinement of the optical mode in the waveguide rib. Research at CERN [3], [4] showed that such a phase shifter can be made much more tolerant against radiation, if the slab thickness is increased significantly. The downside is a less confined optical mode and a slightly degraded modulator performance.…”
Section: Pos(twepp2019)053mentioning
confidence: 99%
“…The slab thickness of these standard modulators is 120 nm, providing a good confinement of the optical mode in the waveguide rib. Research at CERN [3], [4] showed that such a phase shifter can be made much more tolerant against radiation, if the slab thickness is increased significantly. The downside is a less confined optical mode and a slightly degraded modulator performance.…”
Section: Pos(twepp2019)053mentioning
confidence: 99%
“…Until now, radiation effects studies on PICs have been primarily limited to studies of TID [1,3,4,5], however, recent studies have demonstrated that SEEs may also be a significant area of study for PICs [2]. In particular, there is currently a lack of ability to simulate and model the time domain transient effects that occur as a result of an ionizing particle striking an optical component.…”
Section: 63mentioning
confidence: 99%
“…al. [3] Other research has been done in identifying the mechanisms that cause degradation of the performance of a Mach-Zehnder modulator [4] and to model the effects caused by the TID [1]. A limited set of work has studied SEEs in PICs…”
Section: Research Of Single-event Effects In Photonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that silicon photonics Mach-Zehnder modulators (MZMs) are relatively insensitive to neutron radiation, but show strong degradation with ionizing X-ray radiation. It was further presented, that with customized MZM designs, increasing the rib height of MZMs (shallow-etch device), the resistance against X-ray radiation can be improved [2,3,4,5,6]. Recently, the influence of forward biasing on the radiation hardness was reported and a strong post-irradiation annealing effect was demonstrated [7].…”
Section: Introductionmentioning
confidence: 99%